The Effect of Training, Workplace Incivility, Perceived Supervisor Support, Job Satisfaction on Organizational Identification and Their Influence on Employee Performance and Turnover Intention - Muhammad Fikri Rahadian Utama; Justine Tanuwijaya (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze the factors that influence employee performance and employee turnover intention with the application of factors in the form of training, workplace rudeness, perceived supervisor support, job satisfaction, and organizational identification for employees of one of the companies engaged in renewable energy in Jakarta. The data processing method uses structural equation modelling (SEM). The results are that there is no influence between training and workplace rudeness on organizational identification. There is an effect of perceived supervisor support and job satisfaction on organizational identification. There is also an influence between organizational identification on employee performance. There is no effect on employee performance on organizational identification—turnover intentions. Therefore, employee performance needs to be improved so that employee turnover does not occur. Employee performance improvement can be supported by supporting variables related to organizational identification.